Тороидальные наноструктуры углерода. Одностенные 4-, 5- и 6-гранники и нанокольца - Харламов, А. И.; Лойченко, С. В.; Кириллова, Н. В.; Каверина, С. Н.; Фоменко, Вениамин Васильевич (My University, 2004)
Впервые наблюдались тороидальные наноструктурные образования углерода. Карбоновые наноструктуры формировались в следствии реакции полимеризации бензола благодаря частицам металла как акцептора электронов. Предложена модель процесса.

Carbon nanostructures of toroidal shape are first obtained. It is shown that carbon nanopolyhedrons and nanorings are thermostable as carbon nanotubes. An original model of nucleation and growth of carbon molecules is proposed, in which the of hydrocarbon decomposition up to carbon and dissolution of carbon in metal particles as intermediate are not considered. Carbon nanostructures are formed due to the benzene polymerization reaction on the surface, in particular, of a metal particle as electron acception.
Keywords: углерод; карбон; carbon; нанотрубки; тороидальные; углероды; разложение; nanotubes; toroidal; shape; hydrocarbon; decomposition; кафедра харчової хімії